2018
DOI: 10.1061/(asce)gt.1943-5606.0001827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rubber Crumbs on the Cyclic Behavior of Steel Furnace Slag and Coal Wash Mixtures

Abstract: The practical application of waste materials such as steel furnace slag (SFS) and coal wash (CW) is becoming more prevalent in many geotechnical projects. While adding rubber crumbs (RCs) from recycled tires into mixtures of SFS and CW not only solves the problem of large stockpiles of waste tires, it also can provide an energy-absorbing medium that will reduce vibration and prevent track degradation. Thus, the engineering insight into the effect that rubber crumbs have on the dynamic behavior of SFS þ CW þ RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…Qi et al [55] established an energy-consumption flowchart based on the comprehensive properties of SFS + CW + RC mixtures ( Fig. 5).…”
Section: Energy-absorbing Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Qi et al [55] established an energy-consumption flowchart based on the comprehensive properties of SFS + CW + RC mixtures ( Fig. 5).…”
Section: Energy-absorbing Analysismentioning
confidence: 99%
“…The inclusion of rubber shock mats decreases the hard interface between the ballast aggregates and other track components, such as the sleepers or underlying formations, and allows the particles bedding into softer pads, thus enhancing the area of contact of the aggregates and minimising the inter-particle contact forces [42,47,51]. Moreover, indirect methods to reduce the degradation of ballast by using rubber products in the sub-ballast layer have also been proposed in recent times, such as replacing the traditional sub-ballast with an energy-absorbing layer composed of waste materials, including coal wash, steel furnace slag and rubber crumbs [28,55], and using a capping layer confined with recycled rubber tyre cells [17]. In this paper, some of these methods involving the use of recycled rubber products in rail tracks will be presented and discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane correction was applied for the test results obtained under ′ 3 = 10 , while for higher effective confining pressures the membrane effect was ignored as the error was less than 3% (Indraratna et al 2018;Lackenby et al 2007). In Australia, there are many low-lying coastal tracks in which the subballast is usually saturated by the high groundwater table (Qi et al 2018c). To predict the stress-strain behaviour more accurately, the influence of (%) on the critical state of SFS+CW+RC specimens compacted at 95% of their maximum dry density and sheared under three different effective confining pressures ( ′ 3 = 10, 40, and 70 ) have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Tsang et al (2012) found using rubber-soil mixture as an alternative seismic isolation material could significantly reduce the horizontal and vertical acceleration and displacements. The cyclic loading tests on rubber-waste mixtures conducted by Qi et al (2017b) reveal that the inclusion of RC could increase the damping ratio of the waste mixtures.…”
Section: Introductionmentioning
confidence: 99%